Opinion of French nephrologists on renal replacement therapy: survey on their personal choice - Lorcy, Nolwenn (Clin Kidney J, 2015)
BACKGROUND: In France, like in most developed countries, peritoneal dialysis (PD) is less used than haemodialysis (HD). This is not based on medical evidence supporting HD superiority. As the practitioner's opinion is important to patients and may influence their treatment choice, we conducted a survey among French nephrologists to determine which renal replacement therapy (RRT) they would choose if they had end-stage renal disease (ESRD). METHODS: We e-mailed a self-administered questionnaire to all members of the French-speaking Nephrology Society between 19 October 2008 and 12 January 2009. We then selected from the French Renal Epidemiology and Information Network (REIN) registry a reference population of 20- to 64-year-old patients with ESRD who began RRT [HD, PD or pre-emptive transplantation, (PT)] in 2008. RESULTS: The survey response rate was 17.8%. Results showed that 59.6% of respondents chose early inscription on the transplantation waiting list in view of PT, 20.2% selected HD and 20.2% selected PD. When dialysis was the only choice, 50.2% chose HD and 49.8% chose PD. Younger nephrologists (≤44 years old) selected PD more frequently than older nephrologists (≥45 years old) (58.9 versus 40.5%; P < 0.01). Similarly, PD was chosen more often by nephrologists from regions with ‘more PD’ than from regions with ‘less PD’ (79.0 versus 48.8%; P < 0.05). The nephrologists' choices were different from the RTT distribution among the reference population: 81.7% HD, 10.1% PD and 8.2% PT. CONCLUSION: Our survey on the theoretical choice of RTT suggests that the low PD rate in France cannot be explained by a negative opinion of PD among French nephrologists.